2006
DOI: 10.1007/s10591-006-9010-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Relationship Satisfaction: Importance of Communication Skills

Abstract: The present study aimed to investigate the association between communication skills and relationship satisfaction, after having controlled for some other important associates of relationship satisfaction, such as attachment styles and various problem-solving skills including sense of control, confidence, and attitudes of approach-avoidance. One-hundred-forty-two university students who were either currently involved in a romantic relationship, or who had a romantic relationship in the past participated in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 25 publications
3
27
0
8
Order By: Relevance
“…Couples that use effective problem-solving strategies tend to preserve relationship quality and satisfaction, even when navigating inevitable problems that arise (Sullivan et al 2010). Ultimately, couples that can resolve problems amicably are more likely to maintain high levels of relationship satisfaction and are less likely to have disagreements escalate to destructive forms of conflict or experience separation and divorce (e.g., Eğeci and Gençöz 2006; Markman et al 1993). …”
Section: Introductionmentioning
confidence: 99%
“…Couples that use effective problem-solving strategies tend to preserve relationship quality and satisfaction, even when navigating inevitable problems that arise (Sullivan et al 2010). Ultimately, couples that can resolve problems amicably are more likely to maintain high levels of relationship satisfaction and are less likely to have disagreements escalate to destructive forms of conflict or experience separation and divorce (e.g., Eğeci and Gençöz 2006; Markman et al 1993). …”
Section: Introductionmentioning
confidence: 99%
“…For example, if an individual discloses information of great depth early in a relationship, he or she would probably be viewed as incompetent and disliking would result. This is supported by previous research that demonstrates the importance of communication competence in the success of both friendships (Holmstrom, 2009) and romantic relationships (Egeci & Gençöz, 2006). In organizational communication, Madlock (2008) found that perceptions of communication competence by leaders developed from use of a relational leadership style, as did liking, which further supports the position that relational leadership, liking, and appropriateness are related.…”
Section: Self-disclosure Liking and Appropriatenesssupporting
confidence: 77%
“…They view themselves and evaluate others positively. These people report greater marital satisfaction and adjustment (Banse, 2004;Egeci & Gencoz, 2006;Ozmen ve Atik, 2010;Scott & Cordova, 2002). In this study, it was found that the relationship between marital adjustment and psychological symptoms is more stronger among individuals who have secure attachment style.…”
mentioning
confidence: 65%